2018
DOI: 10.1038/s41556-018-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct generation of human naive induced pluripotent stem cells from somatic cells in microfluidics

Abstract: Induced pluripotent stem cells (iPSCs) are generated by expression of transcription factors OCT4, SOX2, KLF4 and cMYC (OSKM) in somatic cells. In contrast to murine naïve iPSCs, conventional human iPSCs are in a more developmentally advanced state-called primed pluripotency. Here we report that human naïve iPSCs (niPSCs) can be generated directly from less than 1000 primary human somatic cells without stable genetic manipulation by delivery of modified messenger RNAs with microfluidics. Expression of OSKM in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 60 publications
11
107
0
1
Order By: Relevance
“…We found that supplementation with XAV markedly improves the efficiency of reprogramming to the naïve state, in line with observations during resetting of conventional PSC (Guo et al, 2017). This may be a key difference from previous reports that found low efficiency of naive reprogramming using media that typically included the GSK3 inhibitor CH (Giulitti et al, 2019;Kilens et al, 2018;Liu et al, 2017). Our analysis shows that the presence of CH inhibits reprogramming to naïve status.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We found that supplementation with XAV markedly improves the efficiency of reprogramming to the naïve state, in line with observations during resetting of conventional PSC (Guo et al, 2017). This may be a key difference from previous reports that found low efficiency of naive reprogramming using media that typically included the GSK3 inhibitor CH (Giulitti et al, 2019;Kilens et al, 2018;Liu et al, 2017). Our analysis shows that the presence of CH inhibits reprogramming to naïve status.…”
Section: Discussionmentioning
confidence: 65%
“…Transgene-free naïve iPSC have also been produced using chemically modified RNAs, but the efficiency of this approach was reported to depend on cell confinement in a microfluidic chamber (Giulitti et al, 2019), which restricts general application. In contrast, our results demonstrate that reprogramming to the naïve state can be highly efficient using unmodified RNAs in standard cell culture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the existing nonintegrating methods, such as small molecules, mRNA, or episomal transfection, yield reprogramming efficiencies lower than viral transduction. Yet, we foresee that the development of miniaturized microfluidic devices enabling massive scale-down and parallelization of iNSC generation will further reduce the production costs [95] and promote a widespread clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Bi-allelic expression of imprinted genes will indicate LOI. Bi-allelic expression of X-linked genes may indicate reactivation of the X chromosome, as expected in the early embryo 18 or in naive pluripotent stem cells 12,13,19,20 , X chromosome erosion, as observed after extensive culture of pluripotent cells 21 , or simply escape of single genes from the XCI mechanisms, as recently documented in somatic cells 22,23 .…”
Section: Mainmentioning
confidence: 71%